Test Case Prioritization in Continuous Integration environments: A systematic mapping study - Prado Lima, Jackson A.; Vergilio, Silvia R. (Information and software technology, 2020)
Context: Continuous Integration (CI) environments allow frequent integration of software changes, making software evolution more rapid and cost-effective. In such environments, the regression test plays an important role, as well as the use of Test Case Prioritization (TCP) techniques. Such techniques attempt to identify the test case order that maximizes certain goals, such as early fault detection. This research subject has been raising interest because some new challenges are faced in the CI context, as TCP techniques need to consider time constraints of the CI environments. Objective: This work presents the results of a systematic mapping study on Test Case Prioritization in Continuous Integration environments (TCPCI) that reports the main characteristics of TCPCI approaches and their evaluation aspects. Method: The mapping was conducted following a plan that includes the definition of research questions, selection criteria and search string, and the selection of search engines. The search returned 35 primary studies classified based on the goal and kind of used TCP technique, addressed CI particularities and testing problems, and adopted evaluation measures. Results: The results show a growing interest in this research subject. Most studies have been published in the last four years. 80% of the approaches are history-based, that is, are based on the failure and test execution history. The great majority of studies report evaluation results by comparing prioritization techniques. The preferred measures are Time and number/percentage of Faults Detected. Few studies address CI testing problems and characteristics, such as parallel execution and test case volatility. Conclusions: We observed a growing number of studies in the field. Future work should explore other information sources such as models and requirements, as well as CI particularities and testing problems, such as test case volatility, time constraint, and flaky tests, to solve existing challenges and offer cost-effective approaches to the software industry.